Kesehatan dalam Pandangan Hukum Islam - Iman Jauhari (Universitas Syiah Kuala, 2011)
ABSTRACT: The purpose of this paper examines Islam and human mental health, health is one of the maqhasid syariah, and health in the study of Islamic law. The method used is the approach to library research with content analysis of the various references relevant to the subject matter covered. The results indicate discussion of Islam and the health of the human spirit can not be separated, because the most able to help people when you get a load and disasters are Allah SWT then ask Allah SWT to be given the power to deal with any heavy trials. Maintaining healthy (mind) is one of the maqhasid syari'ah. Islamic law applies flexible in addressing the technological advancement of health. Nevertheless, there remain limitations and restrictions, such as blood transfusion is permissible based on the loose in an emergency. Likewise, transplantation of animal organs in human organs, in a state of emergency can be done with the record organs that organ must necessarily have a part in the excreta (najis), as well as the organ in the human body. While human cloning is forbidden in Islam because the Al-Qur'an surat At-Tin: 4, states, which means: “Sesungguhnya Kami telah menciptakan manusia dalam bentuk yang sebaik-baiknya”. (Verily We created man in his best form). Health Views In Islamic Law